The effect of gradual self-control of task difficulty and feedback on learning golf putting - Jalalvand, M.; Bahram, A.; Daneshfar, A.; Arsham, S. (Research Quarterly for Exercise and Sport, 2019)
Purpose: This study aimed to examine the effect of gradual self-control of task difficulty and feedback on accuracy and movement pattern of the golf putting sport skill. Method: Sixty students were quasi-randomly assigned to four groups under a varying combination of the two factors of task difficulty control (self-controlled or yoked) and feedback control (self-controlled or yoked). The participants in the two groups (dual-factor gradual self-control and self-controlled task difficulty group) that granted control over task difficulty in the acquisition phase were told they could choose any of the pre-set distances from the target. All groups were given 100% feedback in the first half of the acquisition phase, but the participants in the two groups (dual-factor gradual self-control group and self-controlled feedback) that could control their feedback were told that in the second half of the acquisition phase they would be able to ask for feedback when needed. The practice schedule of each member of the dual-factor gradual self-control group was used as a basis to plan the practice of predetermined distances and feedback presentation to the corresponding participants in the yoked conditions. Results: ANOVA with repeated measures showed that the practice method involving gradual self-control of two factors had a positive impact on accuracy and movement pattern of golf putting in the retention and transfer tests compared to other methods (ps < .05). Conclusion: The advantages of self-control practice presumably come from better adjustment of challenge points by the learner in the course of the practice.